Checklist of the dragonflies (Odonata) of Iran with new records and notes on distribution and taxonomy - Schneider, Thomas; Ikemeyer, Dietmar; Müller, Ole; Dumont, Henri J. (Zootaxa, 2018)
Iran has a complex dragonfly fauna influenced by contacts and overlaps of different geographical zones. Its fauna is dominated by Eurosiberian taxa. However, the SE Province Sistãn-va-Baluchestãn is rich in oriental species, many of which having their western distribution limit in Iran. In NE-Iran, Irano-Turanian elements live and in the S- and SW-Iran African species are found. The Iranian Odonata fauna seems well studied, however, a closer look reveals many uncertainties and confusion, some records coming clearly from misidentification whereas other, which were missing proofs of correct identification remains to be confirmed. Even today, every new collecting trip reveals species new for Iran whereas species new for science are still detected, although rarely. In this checklist we include seven taxa new for Iran: Stylurus ubadschii (although a male of uncertain origin is recorded in Schmidt (1954), Ischnura senegalensis (although two uncertain records were published by Martin (1912) and Schmidt (1954), Coenagrion ponticum, C. lunulatum, C. pulchellum, Lestes macrostigma, and Calopteryx splendens tschaldirica. We critically checked all available data, including all published records. Fourteen taxa have been rejected, or placed in the category for need of confirmation. Till the end of 2017, 100 autochthonous taxa of dragonflies and two migratory species could be confirmed to be or have been present in Iran. We provide distribution maps, created after evaluation of published data and containing our own data from 12 trips to Iran, travelling over 35000 km in the country. Over 200 new localities are integrated. Taxonomic confusion is reduced by rejecting the following taxa for Iran: Calopteryx splendens mingrelica, C. hyalina, Erythromma najas, Aeshna cyanea, Gomphus davidi, and Sympetrum sinaiticum. We regard the taxa Gomphus amseli and G. schneiderii transcaspicus as synonyms of G. schneiderii, and Onychogomphus forcipatus lucidostriatus as a synonym of O. f. albotibialis.